An Assessment of Nigeria’s Democracy through the Lens of John Locke’s Political Thought (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The quest for power is an inherent part of human inclination and existence. As a societal and political being, man seeks and exercises this power within his society. Once power is sought and legitimately invested by the people, those in authority often exercise it in an egocentric manner. Consequently, there is a tendency for this power to be abused. The abuse of political power in Nigeria is a deeply entrenched issue, rooted in a legacy of authoritarianism, corruption, and institutional fragility. This study investigates the phenomenon through John Locke’s political theory, offering a critical reflection on the legitimacy and limits of authority in the Nigerian political context. Furthermore, Locke’s principles, centred on the social contract, the consent of the governed, and the right to resist tyranny, provide a compelling framework for understanding the failures of governance and the erosion of democratic values. The study employs analytical methods to examine how Nigerian politicians consistently violate the foundational tenets of Locke’s philosophy, exercising power without accountability and undermining the rule of law. The findings reveal a persistent disconnect between the governed and those in authority, resulting in systematic injustice and political instability. The study therefore concludes that Locke’s theory is profoundly relevant to Nigeria’s political evolution, offering not only a critique of current governance but also a pathway toward restoring legitimacy, empowering citizens, and transforming power into a force for justice and collective progress.